Pendeteksian Kecurangan Pelaporan Keuangan Dengan Menggunakan Pentagon Fraud Pada BUMN Yang Terdaftar Di Bursa Efek Indonesia - Dewi, Ni Putu Gina Puspita; Yudantara, I Gede Agus Pertama (Universitas Pendidikan Ganesha, 2020)
This study aimed at analyzing the effects of pressure, opportunity, rationalization, competence and arrogance both concurrently and relatively on fraudulent financial reporting on state-owned companies registered on the Indonesia Stock Exchange in the 2014-2018 period. The secondary data acquired from yearly reports and financial statements of the state-owned companies listed on the Stock Exchange in the 2014-2018 period were applied in this study. The sample representative method used purposive sampling so that 17 companies were used in this study. Data analysis method used in this study were descriptive statistical analysis and logistic regression analysis using SPSS 20. The results of this study convey the simultaneous the pressure, the opportunity, the rationalization, the competence, and the arrogance influence the detection of fraudulent financial reporting notably. The trial results partially indicate that arrogance which is substituted by the frequency of the number of CEO photos has a significant positive outcome in distinguishing fraudulent financial reporting, while the pressure variable (leverage ratio), the opportunity (percentage of the number of independent audit board), the rationalization (change of public accountants) and the competence (changes directors) partially has no effect in the detection of fraudulent financial reporting.